Theoretical basis for curriculum development in Polish pedagogy between 1918 and 1939 - Roman Ceglarek (Edukacja Ustawiczna Dorosłych, 2021)
The paper deals with issues concerning the theory of curriculum construction in the Second Republic of Poland. The curricula were inspired by the achievements and development of academic disciplines dealing with the upbringing and education of children and young people. In their fundamental assumptions they reflected the achievements of the new pedagogical trends, psychological theories and concepts developing in the world at that time. Drawing on their achievements, some Polish teachers took up the issue of curricula in their academic reflection, creating a theoretical basis for their construction for all types of schools, thus contributing to the organisation of the educational reality after Poland regained its independence.